MBCL-44. THE MOLECULAR AND CLINICAL LANDSCAPE OF INFANT MEDULLOBLASTOMA (iMB): RESULTS AND MOLECULAR ANALYSIS FROM A PROSPECTIVE, MULTICENTER PHASE II TRIAL (SJYC07). Issue 2 (22nd June 2018) - Robinson, Giles W; Rudneva, Vasilisa A; Buchhalter, Ivo; Billups, Catherine A; Waszak, Sebastian M; Smith, Kyle; Bowers, Daniel C; Bendel, Anne; Fisher, Paul; Partap, Sonia; Crawford, John; Hassall, Tim; et al.
Abstract: BACKGROUND: iMB has inferior survival to older children principally due to radiation-sparing therapy. To better understand which patients may benefit from radiation-sparing protocols, we describe the molecular landscape of iMB and report the iMB outcome on the SJYC07 trial designed to defer, reduce, or delay radiation exposure. METHODS: We assembled a molecular cohort of 190 iMBs and a SJYC07 trial cohort of 81 iMBs. Tumors were sub-classified into molecular subgroups based on DNA methylation profiles and overlaid with mutations and copy-number alterations. PFS and OS for the SJYC07 cohort was estimated across clinical risk groups, consensus molecular subgroups, and in the context of novel MB subtypes. RESULTS: Computational analysis of DNA methylation array data divided iMB into three of the four consensus subgroups: SHH, G3, and G4 (absent WNT). Clinical outcome of iMBSHH was superior to iMBGroup3/Group4 (5-year PFS: 51 ± 8% vs 11 ± 10%, P<0.001; 5-year OS: 72 ± 8% vs 51 ± 12%, P<0.05). t-distributed stochastic neighbor embedding (t-SNE) analysis recognized two subtypes of iMBSHH (iMBSHH-I and iMBSHH-II ) and distributed iMBGroup3/Group4 into eight recently described subtypes (I-VIII). 5-year PFS of iMBSHH-II surpassed iMBSHH-I (75 ± 10% vs 28 ± 10%, P=0.003) and exceeded 90% in low-risk iMBSHH-II (<3y, M0, R0, DN/MBEN). CONCLUSION: Through integrative genomics, we described the molecular landscape of iMB. Application of these data to a trial cohort identifies: a low-risk SHH-subtype (iMBSHH-II ) that exhibits excellent PFS in the absence of radiation, intra-ventricular chemotherapy, and high-dose chemotherapy; a high-risk SHH-subtype (iMBSHH-I ); and very poor PFS for iMBGroup3/Group4 . These findings will shape risk stratification on future iMB trials.